Toward a Modern Japanese Theatre : Kishida Kunio - Rimer, J. Thomas (Book collections on Project MUSE., 1974)
Long accustomed to writing in the tradition of the flamboyant kabuki, Japanese dramatists had a more difficult struggle in modernizing their art than did writers of fiction and poetry. The work of Kishida Kunio, however, established and matured modern Japanese drama, modeled on the western psychological drama of Ibsen and Chekhov.J. Thomas Rimer traces the initial modernization efforts undertaken by the first generation of Japanese playwrights of the shingeki, or "New Theatre.'" His study then concentrates on the work of Kishida Kunio, the most important figure in the Japanese theatre of the 1930s and 1940s. Kishida, who studied with the well-known French director Jacques Copeau in 1921, returned to Japan with the goal of establishing a modern drama of psychological dimensions for the Japanese theatre. His work demonstrated his talent as a playwright and laid the foundation for later modern Japanese playwrights.Originally published in 1974.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.